Comparison of the acute physiological and perceptual responses between resistance-type and cycling high-intensity interval training - Mao, Jun; Wang, Tao; Zhang, Li; Li, Qing; Bo, Shumin (Frontiers in Physiology, 2022)
Purpose: The purpose of the present study was to compare the acute physiological and perceptual responses between resistance-type high-intensity interval training（R-HIIT）and cycling high-intensity interval training (C-HIIT). Methods: Twelve healthy and active men randomly performed C-HIIT and R-HIIT. The C-HIIT protocol was performed on a cycle ergometer and consisted of ten 60s working intervals at 90% PPO separated by a 60s active recovery at 25% PPO. The R-HIIT protocol consisted of ten 60s working intervals (barbell back squat with a load of 20% bodyweight, maximum 30 reps) separated by 60s passive recovery period in an unloaded standing position. Oxygen consumption (VO2), heart rate (HR), energy expenditure (EE) and rating of perceived exertion (RPE) were measured during exercise. Blood lactate concentration (Blac), serum testosterone and cortisol, and heart rate variability (HRV) were measured before and after exercise. Results: Peak (P<0.05) and average relative VO2 (P<0.001), aerobic (P<0.001) and total EE (P<0.05) were higher during C-HIIT compared to R-HIIT. Blac after exercise (P<0.05) and anaerobic glycolytic EE (P<0.05) during exercise were higher in R-HIIT compared to C-HIIT. No differences (P>0.05) in peak and average HR, serum testosterone and cortisol, HRV, and RPE responses were observed between C-HIIT and R-HIIT. Conclusions: The R-HIIT protocol can elicit similar cardiovascular, hormones, and perceptual responses as C-HIIT but with a higher contribution to the anaerobic glycolysis energy system. In contrast, C-HIIT is superior to R-HIIT for increasing oxygen consumption during exercise. Therefore, the two types of HIIT may lead to different metabolic and neuromuscular adaptations.